TAWURAN DALAM TINJAUAN GANGGUAN KEJIWAAN - Andina, Elga (Jurnal Aspirasi, 2012)
The increase in juvenile brawl aggressively alarming. As it occurred not only inbig cities, but also in rural, the acts have become major concern in psychological work. This qualitative study collects data from various mass media reports from 2011 to 2012 in order to determine two major themes that encourage the brawl. There are two reasons to start a brawl: the state of idleness and the feeling of helplessness. The root of aggressive act is suspected to be an indicator for mental disorder. That’s why any intervention is needed to prevent the acts to transform in to serious illness. Character building is believed to be the tool to help students developing resilience and self-control for mentally health self. Students paired in character education are hoped to maintain positive behavior. DPR RI must pull out the Mental Health Act to support the system.